2018
DOI: 10.1016/j.bbamem.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alterations of the E. coli lipopolysaccharide layer on membrane permeabilization events induced by Cecropin A

Abstract: The outermost layer of Gram negative bacteria is composed of a lipopolysaccharide (LPS) network that forms a dense protective hydrophilic barrier against entry of hydrophobic drugs. At low μM concentrations, a large family of cationic polypeptides known as antimicrobial peptides (AMPs) are able to penetrate the LPS layer and permeabilize the outer membrane (OM) and the cytoplasmic membrane (CM), causing cell death. Cecropin A is a well-studied cationic AMP from moth. Here a battery of time-resolved, single-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Next we performed live-cell imaging experiments to measure the time course of Cecropin A action on single E. coli cells growing exponentially or in stationary phase. These experiments were performed using the imaging assays described in our previous work [14]. Briefly, for E. coli cells in exponential growth phase, a solution of Cecropin A and 5 nM Sytox Orange in fresh EZRDM flowed through the microfluidic chamber containing plated mid-log cells (Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Next we performed live-cell imaging experiments to measure the time course of Cecropin A action on single E. coli cells growing exponentially or in stationary phase. These experiments were performed using the imaging assays described in our previous work [14]. Briefly, for E. coli cells in exponential growth phase, a solution of Cecropin A and 5 nM Sytox Orange in fresh EZRDM flowed through the microfluidic chamber containing plated mid-log cells (Methods).…”
Section: Resultsmentioning
confidence: 99%
“…There are studies indicating that the LPS layer plays a crucial role in the attraction and control of AMPs binding to the surface of Gram-negative bacteria (Ding et al 2003;Papo and Shai 2005;Agrawal and Weisshaar 2018). Ebbensgaard et al (2015) demonstrated protective effect of LPS against antimicrobial activity of many AMPs (including cecropin B and cecropin P1) manifested by a higher susceptibility of the E. coli LPS defective mutants in comparison with their parental strains: O6 serotype E. coli ATCC 25,922 and rough E. coli BW25113K-12.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Agrawal and Weisshaar (2018) using single-cell fluorescence microscopy showed that deletion of sugar layers or/and phosphate groups from the core oligosaccharide in E. coli K-12 LPS accelerated permeabilization of the outer membrane and cytoplasmic membrane by cecropin A. They postulated that the core oligosaccharide part of LPS functions as a kinetic barrier slowing cecropin A passage to the lipid A leaflet (Agrawal and Weisshaar 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We mixed the bacterial solution with the Mueller-Hinton broth, and the potential bacterial increase was checked by examining the turbidity after 24 h of incubation at 35 °C. The value of cecropin A, 46 pardaxin P5, 47 and SL-37 29 have previously reported and used the value in this study.…”
Section: Methodsmentioning
confidence: 99%